A unidade metafísica do ser e a relação entre os humanos e os demais animais no pensamento de Schopenhauer - Franco, Eduardo Ferraz (2014)
The finding that the world known by the human cognitive apparatus leads Schopenhauer to unpower and equip the scope of intelligence and reason. If by these pathways the knowledge of the thing-in-itself is impossible, Schopenhauer finds it in the intimate feeling of the will. The intimate feeling of the essence of the self is expanded to the world that can only be a metaphysical unity, but it appears as self discord, imperfection. It is the possibility of visualizing the metaphysical unity of Being which enables the philosopher to extend the scope of consideration of human good actions to the animals.